2009
DOI: 10.1108/00197850910983938
|View full text |Cite
|
Sign up to set email alerts
|

Training strategies for an aging workforce

Abstract: PurposeThe purpose of this paper is to explore how organizations might support older workers' learning.Design/methodology/approachThe paper highlights an incoming HR challenge (training older workers), conducts a review of corporate responses in Europe, and then identifies lessons. Examples are drawn from the case study database of the European Foundation for the Improvement of Living and Working Conditions.FindingsThe paper identifies four lessons. The first is to adopt a targeted approach, which involves bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Major functions of the mentor–mentee relationship include teaching, personal support, and organizational intervention (Zey, 1991). Most researchers emphasize the role of mentoring in passing on experience and knowledge from experts to new-entries, and the benefits to corporates adopting a mentoring system (Freedman, 2009; Koc-Menard, 2009; Lindbo & Shultz, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Major functions of the mentor–mentee relationship include teaching, personal support, and organizational intervention (Zey, 1991). Most researchers emphasize the role of mentoring in passing on experience and knowledge from experts to new-entries, and the benefits to corporates adopting a mentoring system (Freedman, 2009; Koc-Menard, 2009; Lindbo & Shultz, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The program they developed later demonstrated that mentorship was helpful to these retirees in developing an adaptive lifestyle after retirement (Stancliffe, Bigby, Balandin, Wilson, & Craig, 2015). Koc-Menard (2009) highlighted the benefits for corporates to make use of the mentors’ knowledge and experience to train successors, and systematically develop its capacity in supporting retirees. Some studies focused on the effectiveness of senior mentors who are retired in coaching the younger generations in their professional development (Bates, Cohan, Bragg, & Bedinghaus, 2006; Eleazer, Stewart, Wieland, Anderson, & Simpson, 2009; Eleazer, Wieland, Roberts, Richeson, & Thornhill, 2006; Hoffman, Gray, Hosokawa, & Zweig, 2006; Wieland & Eleazer, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Here we have considered early career stage between 20 and 40; middle career stages between 40 and 54, and late career stage 55 and above. In an effort to set a threshold to define the older worker category, as anyone over age 55 (Finkelstein et al 1995;Koc-Menard 2009).…”
Section: Social Opportunitiesmentioning
confidence: 99%
“…Pitt-Catsouphes, 2007) of integrating age-diverse employees into sustainable and efficient organizational systems. This (Zwick, 2011), suggesting a need for age-customized programs (Koc-Menard, 2009). This research suggests the need for training that improves the outcomes of first interactions between older employees and new colleagues, including managers, peers and subordinates.…”
Section: Discussionmentioning
confidence: 86%